2021
DOI: 10.1021/acs.jctc.1c00816
|View full text |Cite
|
Sign up to set email alerts
|

Local-Field Effects in Linear Response Properties within a Polarizable Frozen Density Embedding Method

Abstract: In this work, we present a polarizable frozen density embedding (FDE) method for calculating polarizabilities of coupled subsystems. The method (FDE-pol) combines a FDE method with an explicit polarization model such that the expensive freeze/thaw cycles can be bypassed, and approximate nonadditive kinetic potentials are avoided by enforcing external orthogonality between the subsystems. To describe the polarization of the frozen environment, we introduce a Hirshfeld partition-based density-dependent method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…PDE (and PDE-X) instead rely on a classical description of environment polarization through an induced-dipole model, which is computationally more affordable. Recently, methods that combine classical polarization models to describe polarization in FDE have emerged, for example, with the three-layer QM/FDE/fluctuating charges model by Egidi et al and the polarizable FDE-EO by Pal et al , …”
Section: Introductionmentioning
confidence: 99%
“…PDE (and PDE-X) instead rely on a classical description of environment polarization through an induced-dipole model, which is computationally more affordable. Recently, methods that combine classical polarization models to describe polarization in FDE have emerged, for example, with the three-layer QM/FDE/fluctuating charges model by Egidi et al and the polarizable FDE-EO by Pal et al , …”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the challenging nature of the SERS phenomenon, impressive theoretical advances have been carried out in just few decades after its discovery by Fleischmann, Hendra, and McQuillan . Among many achievements, it is worth to highlight the SERS selection rules derived by Lombardi and Birke by incorporating Herzberg–Teller vibronic coupling into Albrecht expression of the transition polarizability , and methodological advances led by the Jensen group. …”
Section: Introductionmentioning
confidence: 99%
“…We denote PE models with this effect included as PE . There is no corresponding term for FDE models, although extensions have been suggested that include differential polarization. ,, Most of them are, however, rather computationally demanding or require embedded excited-state densities, which are somewhat tedious to obtain for TD-DFT methods …”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Also in the standard PE scheme, the local field effect is not incorporated. It’s effect on the oscillator strengths can, however, approximately be accounted for by adding an external effective field (EEF) term, ⟨ϕ a | V̂ loc |ϕ i ⟩, to M . , The required operator is defined as loc = prefix∑ italicts boldT t normala false( 1 false) boldR italicts bold-scriptE s uni = prefix∑ t boldT t normala false( 1 false) bold-italicμ ext , t ind where μ ext, t ind is the induced dipole to a unit field, bold-scriptE s uni . This approximate description has thereby an effect on the oscillator strengths only, but does not alter the excitation energies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%